Financial Policy of Government support for semiconductors Industry Globally and in Russia under sanctions - L. G. Cherednichenko; E. S. Novikova; E. V. Golubtsova (Финансы: теория и практика, 2023)
The relevance of this study is determined by the need to develop the domestic semiconductors industry in Russia, taking into account the negative effects both internal and external.The purpose of this paper is to test the hypothesis of the positive impact of the methods used by the state of financial support of domestic companies to acquire advanced technologies in a specific area in the context of a lack of funding and the significant lag of the national semiconductor industry in the world’s leading countries.The target of this study is the analysis of possible tools of state support, including subsidies and grants, and methods of their application for the creation of competitive industry of domestic semiconductor production.The key methods used in this study include the collection and processing of statistical data, their comparative analysis, as well as the elaboration of the regulatory framework on tax regulation in this sector of the economy.The main methods applied in this study are data collection and processing, comparative analysis, and the development of a regulatory framework for tax regulation in this sector of the economy. The authors analyzed the semiconductors industry in the world, including the production of microprocessors and other semiconductor components. The situation in countries such as China, USA, Japan, Europe, Taiwan, India and Russia is discussed in more detail. The main problems with semiconductor industry development in Russia have been revealed. Additionally, researchers have evaluated and outlined fields of federal budget spendings in the industry in the period of years 2022 and 2025.The scientific novelty of this paper is to identify the relationship between the measures of state tax incentives provided to the radio-electronic industry and macroeconomic indicators. Based on that authors have developed evaluation criteria of the relevance and efficiency of fiscal preferences for the analyzed industry which is considered as the result of research.It concluded that the state’s initiatives to promote the radio-electronics industry might provide Russia a chance to catch up to the world’s leading countries in this industry.